2022
DOI: 10.1177/10781552211073345
|View full text |Cite
|
Sign up to set email alerts
|

Immediate severe hypersensitivity reaction to etoposide phosphate: Case report and review of the literature

Abstract: Introduction Hypersensitivity reactions from intravenous (IV) etoposide have been rarely reported, with these being seen more commonly with etoposide than with etoposide phosphate. This is generally explained by the need for polysorbate 80, a known cause of hypersensitivity, as a solubiliser, in the etoposide formulation. Case report We report a 22-year-old male, being treated with adjuvant BEP (bleomycin/etoposide phosphate/cisplatin) for a testicular germ cell tumour. Bleomycin and cisplatin were administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 420 Etoposide (VP‐16) is a commonly used antitumor chemotherapeutic drug that inhibits DNA replication, thereby inhibiting the cell cycle of cancer cells, and promoting cancer cell apoptosis and autophagy. 421 In BrC, the expression level of TRIAP1 was significantly higher in TAM and VP‐16 resistant MCF7 cell lines than in sensitive MCF7 cell lines. 378 PTX, a diterpene alkaloid compound with anticancer activity, is widely used in the treatment of breast, ovarian, and some head and neck, and lung cancers.…”
Section: Oncogene Triap1: a Novel Target Downstream Of P53mentioning
confidence: 91%
See 1 more Smart Citation
“… 420 Etoposide (VP‐16) is a commonly used antitumor chemotherapeutic drug that inhibits DNA replication, thereby inhibiting the cell cycle of cancer cells, and promoting cancer cell apoptosis and autophagy. 421 In BrC, the expression level of TRIAP1 was significantly higher in TAM and VP‐16 resistant MCF7 cell lines than in sensitive MCF7 cell lines. 378 PTX, a diterpene alkaloid compound with anticancer activity, is widely used in the treatment of breast, ovarian, and some head and neck, and lung cancers.…”
Section: Oncogene Triap1: a Novel Target Downstream Of P53mentioning
confidence: 91%
“…Therefore, TAM may play a role in the treatment of cancer 420 . Etoposide (VP‐16) is a commonly used antitumor chemotherapeutic drug that inhibits DNA replication, thereby inhibiting the cell cycle of cancer cells, and promoting cancer cell apoptosis and autophagy 421 . In BrC, the expression level of TRIAP1 was significantly higher in TAM and VP‐16 resistant MCF7 cell lines than in sensitive MCF7 cell lines 378 .…”
Section: Oncogene Triap1: a Novel Target Downstream Of P53mentioning
confidence: 99%
“…However, some commonly used drug excipients that act as preservatives, stabilizers or adjuvants may also cause serious allergic reactions, such as polyethylene glycol (PEG),69 tromethamine (or trometamol),10 gadolinium-based contrast agents11 and ethylenediaminetetraacetic acids 12,13. In addition, polysorbate 80 can also cause allergic reactions, especially oxidation of oleic acid and its derivatives 14,15. Both a randomized controlled trial and a retrospective study confirmed that polysorbate 80 as an excipient reduces blood pressure in patients 16,17.…”
Section: Introductionmentioning
confidence: 99%